2013
DOI: 10.1111/1440-1681.12119
|View full text |Cite
|
Sign up to set email alerts
|

Physiological mechanisms for the increase in renal solute‐free water clearance by a glucagon‐like peptide‐1 mimetic

Abstract: SUMMARY1. The aim of the present study was to clarify the mechanisms mediating the effect of a glucagon-like peptide-1 (GLP-1) mimetic on solute-free water excretion in rats.2. The GLP-1 mimetic exenatide (0.05-5.0 nmol/kg, i.m.), alone and in combination with either a vasopressin V 2 receptor antagonist (15 nmol/kg, i.p.) or vasopressin (0.01 nmol/kg, i.m.), was injected into control and water-loaded (water 10-50 mL/kg, p.o., or 50 mL/kg of 0.6% NaCl, i.p.) rats to evaluate the role of collecting duct water p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 33 publications
0
6
1
2
Order By: Relevance
“…Furthermore, GLP‐1 was able to increase free water clearance even during blockade of the V 2 receptor (Kutina et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, GLP‐1 was able to increase free water clearance even during blockade of the V 2 receptor (Kutina et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experiments showed that after treatment with GLP-1 mimetic under conditions of WL, the volume of the fl uid which fl ows from the proximal tubule to the distal tubule increases due to the decrease in its reabsorption. This parameter is affected by regulatory factors in the following segments of renal tubules [8]. Urine excretion increased to 0.12±0.01 ml/min at the peak of water diuresis under the infl uence of GLP-1 mimetic.…”
Section: Resultsmentioning
confidence: 99%
“…It was interesting to evaluate the effect of this peptide on renal function during alternative shifts in water-salt balance (WSB) due to a water load (WL) or salt load (SL). Our previous experiments have demonstrated that the increase in tubular fl uid infl ow into the distal nephron segment and water-impermeable collecting duct is a component of the mechanism for excretion of water excess after treatment with GLP-1 mimetic under conditions of WL [8].…”
mentioning
confidence: 99%
“…Особенное значение в этом случае имеет увели-чение притока жидкости в дистальный сегмент за счет нормализации всасывания жидкости в проксимальном сегменте нефрона. Недавно в экспериментах нами было показано, что миметик глюкагоноподобного пептида 1, эксенатид, уменьшает объем проксимальной реабсорб-ции и вызывает увеличение притока жидкости в дис-тальный сегмент нефрона и собирательные трубки [5,6]. В клинике при лечении СД2 используют эксенатид в виде препарата Баета ® (Eli Lilly).…”
Section: © сахарный диабет 2016unclassified